IMPACT OF GENERAL WELL-BEING OF CHANDIGARH TEACHERS ON THEIR JOB SATISFACTION - Sudha, Sakshi; Verma, Sohit; Sharma, Anu (INTERNATIONAL JOURNAL OF RESEARCH PEDAGOGY AND TECHNOLOGY IN EDUCATION AND MOVEMENT SCIENCES, 2023)
Male and female high school teachers in both rural and urban areas were surveyed for this study to determine differences in work satisfaction. Two hundred government school educators in the Chandigarh area (one hundred secondary and one hundred elementary school educators) constituted the study's sample. Amar Singh and T.R. Sharma Work Satisfaction Scale was used to assess educator happiness on the job. Compared to their urban colleagues, high school teachers in rural areas report higher levels of work satisfaction. Male high school instructors from either urban or rural areas did not differ from one another. Nonetheless, there are notable differences between rural women and their metropolitan counterparts who are educators.